2021
DOI: 10.1049/rpg2.12085
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐short‐term multi‐step wind power forecasting based on CNN‐LSTM

Abstract: The fluctuation and intermission of large‐scale wind power integration is a serious threat to the stability and security of the power system. Accurate prediction of wind power is of great significance to the safety of wind power grid connection. This study proposes a novel spatio‐temporal correlation model (STCM) for ultra‐short‐term wind power prediction based on convolutional neural networks‐long short‐term memory (CNN‐LSTM). The original meteorological factors at multi‐historical time points of different si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…CNN is a feedforward neural network, which is composed of input layer, convolution layer, pooling layer, (Solas et al 2019). In order to ensure the prediction accuracy of LCWGAN-GP method, convolutional neural network (CNN) with good fitting performance to nonlinear function is selected as the discrimination model to form the nonlinear mathematical relationship function between historical time series data and future wind power prediction value (Wu et al 2021), as shown in Fig. 5.…”
Section: Construction Of Discriminant Modelmentioning
confidence: 99%
“…CNN is a feedforward neural network, which is composed of input layer, convolution layer, pooling layer, (Solas et al 2019). In order to ensure the prediction accuracy of LCWGAN-GP method, convolutional neural network (CNN) with good fitting performance to nonlinear function is selected as the discrimination model to form the nonlinear mathematical relationship function between historical time series data and future wind power prediction value (Wu et al 2021), as shown in Fig. 5.…”
Section: Construction Of Discriminant Modelmentioning
confidence: 99%
“…Noman et al [18] investigated a support vector machine (SVM)-based regression algorithm for predicting wind power in Estonia one day in advance. Wu et al [19] suggested a new spatiotemporal correlation model (STCM) for ultrashort-term wind power prediction based on convolutional neural networks and long short-term memory (CNN-LSTM). The STCM based on CNN-LSTM has been used for the collection of metrological factors at various places.…”
Section: Introductionmentioning
confidence: 99%
“…They compared the predicted power tables with the available data on the actual turbine power output measured in the wind farm. Wu et al [19] studied the effective parameters for optimizing the output power of wind turbines and compared the results with the experimental data available from a wind farm in China. They concluded that the LSTM method can accurately detect values, is very accurate and fast, and is more efficient at predicting values than other existing methods.…”
Section: Introductionmentioning
confidence: 99%